OPTIMASI KUALITAS BRIKET BIOMASSA PADI DAN JAGUNG DENGAN VARIASI CAMPURAN SEBAGAI BAHAN BAKAR ALTERNATIF - Hamidah, Laily Noer; Rahmayanti, Ardhana (Universitas Nahdlatul Ulama Sidoarjo, 2017)
The energy crisis demands the development of an alternative energy that can meet daily needs. The existence of rice straw biomass waste and corncob is a potential to be utilized as bioenergy in the briquettes form. This research was conducted to develop and test the characteristics of biomass briquettes as alternative fuels. Biomass used in this research is rice straw and corn cob. The making of briquettes is done by carbonation and compaction with starch adhesive by 10%. To know the best quality of briquettes, a mixture of rice straw (100%) was used, mixed rice straw: corncobs (25%: 75%, 50%: 50%, and 75%: 25%), and corncobs (100 %). Test parameters used are ash content, volatile matter content, and calorific value. The results showed that briquettes from corncobs were the best briquettes from ash content and volatile matter content of 9.52% and 9.7% respectively. While based on calorific value, briquettes with highest heating value is rice straw briquettes that is equal to 3562 Kcal / kg but has the highest volatile matter and ash content which can decrease the quality of briquette.